Andragogical competence and tutor creativity toward learners’ learning interest in equivalency education programs - Berlina Mukhti; MHD Natsir (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study examined the effects of tutors’ andragogical competence and creativity on learners’ learning interest in equivalency education programs at a Community Learning Center in Pasaman Regency. Seventy-three adult learners participated through total sampling. Data were collected using validated and reliable Likert-scale questionnaires measuring andragogical competence, tutor creativity, and learning interest, and analyzed using correlation and multiple regression. Results indicated that both andragogical competence (β = 0.42, p < 0.01) and tutor creativity (β = 0.35, p < 0.01) significantly influenced learning interest individually, while their combined effect explained 48% of its variance. Learners’ interest was generally moderate, suggesting room for improvement. The findings highlight the importance of developing tutors’ instructional skills and creative strategies to enhance learner engagement. Future research should expand samples and explore additional contextual factors affecting adult learning interest.